Laccase localized in hulle cells and cleistothecial primordia of Aspergillus nidulans. - Hermann, T E (1983)
Several species of the genus Aspergillus form sexual spores within minute (approximately 0.2 mm) spherical shells (cleisthothecia) which are woven from specialized hyphae. Aspergillus nidulans cleistothecia are uniquely characterized by their dark red coloration and an envelope of thick-walled globose cells (hulle cells). By use of a new chromogenic substrate, we have shown that the constitutent hyphae of young cleistothecia and the hulle cells which surround the cleistothecia of A. nidulans exhibit a strong phenoloxidase activity which has the substrate specificity of a laccase. This enzyme (laccase II) is distinct from the previously described phenoloxidase (laccase I) that participates in the synthesis of the conidial pigment of A. nidulans: the two enzymes differ electrophoretically, do not cross-react immunologically, appear at different times during colonial development, and are under different genetic control. Examination of seven additional species of Aspergillus showed that the hulle cells of three acleistothecial species were also laccase positive, whereas the pale or unpigmented cleistothecia of four species (which lack hulle cells) were laccase negative. The relevance of these findings to the role of hulle cells in cleistothecial development is discussed. The presence of histologically detectable laccase in cleistothecial primordia provides a valuable tool, previously unavailable, for quantitating the early stages of sexual development in A. nidulans.